The Influence of Online and Offline Purchases on Customer Loyalty with Customer Satisfaction as an Intervening Variable at Magnesium137 Store Blitar - Ahzam, Alfisyahr; Nugroho, Rusdi Hidayat (International Journal of Economics Development Research (IJEDR), 2024)
The rapid development of the global internet has significantly impacted business and consumer shopping behavior, leading to the emergence of two dominant purchasing methods: online and offline. Each of these methods offers distinct advantages and challenges, which in turn influence customer satisfaction. Satisfied customers are more likely to become loyal, a process shaped by their purchasing experiences. This study focuses on analyzing customer responses to improve the quality and evaluation of a local brand, Magnesium137 Store in Blitar. Utilizing an associative study technique with a quantitative approach, the research surveyed customers who made both online and offline purchases. Data were analyzed using path analysis to examine the effects of these purchasing methods on customer satisfaction and loyalty. The results revealed that both online and offline purchases significantly impact customer satisfaction. However, only offline purchases have a notable effect on customer loyalty, while customer satisfaction plays a crucial role in fostering loyalty.